The Effect of Self-Esteem in Speaking Skills at Papua University - Rajagukguk, Dewi Veranita; Mallipa, Imelda; Siregar, Sartika Yulisa (Universitas Islam Ahmad Dahlan (UIAD), 2025)
English speaking skill is challenging for Indonesian students, it is necessary to identify factor such as self-esteem that contributes significantly to the improvement of this skill. This investigation was conducted on students who have taken speaking class at an English Education department in a University in West Papua. The methods used to collect the data were questionnaire and interview. The instrument for Self-esteem identification and classification adapted the Self Esteem Inventory (CSEI) developed by Ryden (1978). Fifty students (50) students voluntarily participated in this study. Based on the data obtained from the research instruments, it was confirmed that self-esteem played pivotal roles on students’ speaking ability. Those with good and high levels of self-esteem perform better than the students with low self-esteem. Home environment, social interactions, supports, and appreciation were identified as determinant components for the students in this context to the level of their self-esteem in improving their English-speaking ability. Some suggestions and recommendations for future investigations are discussed.